2007
DOI: 10.1093/rheumatology/kem031
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of adalimumab for the treatment of ankylosing spondylitis in the United Kingdom

Abstract: This analysis indicates that adalimumab, when used according to UK treatment guidelines, is cost-effective vs conventional therapy for treating AS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
2
18
1
3
Order By: Relevance
“…and adalimumab (Botteman et al 162 funded by Abbott Laboratories). The three studies published in 2007 are largely based on the economic analyses originally submitted by the manufacturers to NICE as part of the previous multiple TA (TA143).…”
Section: Results Of Review Of Existing Cost-effectiveness Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…and adalimumab (Botteman et al 162 funded by Abbott Laboratories). The three studies published in 2007 are largely based on the economic analyses originally submitted by the manufacturers to NICE as part of the previous multiple TA (TA143).…”
Section: Results Of Review Of Existing Cost-effectiveness Evidencementioning
confidence: 99%
“…The ICERs for alternative time horizons ranged between £27,594 (2 years) and £22,704 (25 years). 162 evaluated the cost-effectiveness of adalimumab versus conventional therapy in patients with active AS from a NHS perspective over a 30-year time horizon. Effectiveness data were derived from pooled data from two Phase III studies in patients with an inadequate response to ≥ 1 NSAID.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic evidence for the use of adalimumab in AS is limited to the models summarized in a NICE technology appraisal (NICE 2007) and one analysis investigating the cost efficacy of adalimumab for treatment of AS in the UK (Botteman et al 2007). The NICE technology appraisal includes a model from the manufacturer of adalimumab, and their own.…”
Section: Economic Evidencementioning
confidence: 99%
“…Four studies [28,[50][51][52] were submitted as part of NICE HTA guidance of adalimumab, etanercept, and infliximab for AS [53] and were further described in a systematic review [15]. The results from those studies showed that the ICERs of etanercept and adalimumab were roughly similar, falling below an assumed willingness-to-pay threshold of £30,000, while the ICER for infliximab was in the range of £40,000-50,000 per QALY.…”
Section: Discussionmentioning
confidence: 99%